Promoting Physical Activity in COPD: Insights from a Randomized Trial of a Web-Based Intervention and Pedometer Use - Wan, Emily S. (Respir Med, 2017)
RATIONALE: Low physical activity is highly prevalent among COPD patients and is associated with increased healthcare utilization and mortality and reduced HRQL. The addition of a website to pedometer use is effective at increasing physical activity; however, the timeline of change and impact of environmental factors on efficacy is unknown. METHODS: U.S. Veterans with COPD were randomized (1:1) to receive either (1) a pedometer and website which provided goal-setting, feedback, disease-specific education, and an online community forum or (2) pedometer alone for 3 months. Primary outcome was change in daily step count. Secondary outcomes included 6MWT distance, HRQL, dyspnea, depression, COPD knowledge, exercise self-efficacy, social support, motivation, and confidence to exercise. Generalized linear mixed-effects models evaluated the effect of the pedometer plus website compared to pedometer alone. RESULTS: Data from 109 subjects (98.5% male, mean age 68.6±8.3 years) were analyzed. At 13 weeks, subjects in the pedometer plus website group had significant increases daily step count from baseline relative to the pedometer alone group (804±356.5 steps per day, p=0.02). The pedometer plus website group had significant improvements in daily step count from baseline beginning in week 3 which were sustained until week 13. In subgroup analyses, the pedometer plus website attenuated declines in daily step count during the transition from summer to fall. No significant differences in secondary outcomes were noted between groups. CONCLUSIONS: A website added to pedometer use improves daily step counts, sustains walking over 3 months, and attenuates declines in physical activity due to season.